PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI METODE SCANNING PADA SISWA KELAS V SD LABORATORIUM UNIVERSITAS NEGERI GORONTALO - Sumarni Mohamad (Jurnal Inovasi, 2011)
This action research aims to increase capability to read comprehension to read method. For process of echancing capability proceeds well, thus this researehis implemented by using action research of Hopkins Model. Subjects in is this research are 17 fifth graders of Laboratoris Primary Sehool of State University of Gorontalo. The research of comprehension reding through scanning method is implemented for a month in teaching year of 2010/2011. Implementation of action research is completed with two learning cycles.